Measuring and assessing the physical impact of beam trawling. (6th April 2015) - Depestele, Jochen; Ivanović, Ana; Degrendele, Koen; Esmaeili, Moosa; Polet, Hans; Roche, Marc; Summerbell, Keith; Teal, Lorna R.; Vanelslander, Bart; O'Neill, Finbarr G.
Abstract: Beam trawling causes physical disruption of the seabed through contact of the gear components with the sediment and the resuspension of sediment into the water column in the turbulent wake of the gear. To be able to measure and quantify these impacts is important so that gears of reduced impact can be developed. Here we assess the physical impact of both a conventional 4 m tickler-chain beam trawl and a "Delmeco" electric pulse beam trawl. We measure the changes in seabed bathymetry following the passage of these gears using a Kongsberg EM2040 multi-beam echosounder and use a LISST 100X particle size analyser to measure the concentration and particle size distribution of the sediment mobilized into the water column. We also estimate the penetration of the gears into the seabed using numerical models for the mechanical interaction between gears and seabed. Our results indicate that the seabed bathymetry changes between ∼1 and 2 cm and that it is further increased by higher trawling frequencies. Furthermore, our results suggest that the alteration following the passage of the conventional trawl is greater than that following the pulse trawl passage. There was no difference in the quantity of sediment mobilized in the wake of these two gears; however, the numerical model introduced in this study predicted that the tickler-chain trawl penetrates the seabed more deeply than the pulse gear. Hence, greater alteration to the seabed bathymetry by the tickler-chain beam trawling is likely to be a result of its greater penetration. The complimentary insights of the different techniques highlight the advantage of investigating multiple effects such as sediment penetration and resuspension simultaneously and using both field trials and numerical modelling approaches.